Rest in peace : a cultural history of death and the funeral home in twentieth-century America - Laderman, Gary, 1962- (OUP E-Books., 2003)
Gary Laderman traces the origins of American funeral rituals, & looks at the increasing subordination of religious figures to the funeral director in the late 20th century, demonstrating that the modern director is very far from Mitford's manipulator of 'The American Way of Death'.